The effect of acute match play loading on hip adductor strength and flexibility in soccer players - Light, N. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Deficits in adductor strength and flexibility are considered risk factors for soccer hip/groin injury, yet little is known about the acute effects of soccer match play on these physical features. The aim of this study was to examine the changes in adductor strength and flexibility before; during and immediately after soccer match play. METHODS: Twenty male university soccer players (mean age 22.35±1.98 years) participated in this field-based, within subject, repeated measures study. Each participant performed three adductor squeeze tests measured using a pressure sphygmomanometer in 0° and 45° hip flexed test positions alongside a bent knee fall out test. Tests were performed before (0 mins) half time (45 mins) and at full time (90 mins) of a competitive match. RESULTS: Adductor strength decreased by 17.7% in 0° test position and 19.1% in 45° test position at 90 minutes of soccer play, whilst BKFO scores increased by 15% indicating a reduction in adductor flexibility. Statistical analysis showed significant effects of time vs. adductor strength and squeeze test position (P=0.005), Positive correlations between time played and BKFO scores, and BKFO scores vs adductor squeeze scores at 0 and 45 minutes (P=0.005) were also observed. CONCLUSIONS: University soccer players exhibit decreased adductor squeeze test and BKFO values as soccer match duration increases. These findings may have implications hip/groin injury management and recovery strategies, post or during soccer matches.